Pengaruh Pemberian Gentamisin pada Dosis Terapi Terhadap Ginjal Tikus Putih (Rattus Norvegicus) - Nyoman Gede Trisna Anandita (Jurnal Health Sains, 2021)
Gentamicin is an aminoglycoside antibiotic often used as bactericide by clinicians when treating patients due to its effectiveness in curing infections. Gentamicin is a broad-spectrum antibiotic, effective in acting against a wire-range of gram-negative bacteria (Pseudomonas, Proteus dan Klebsiella), and is affordably priced. Moreover, there is evidently low tendency for bacteria to develop resistance to Gentamicin. The purpose of this study is to scientifically describe the effect of therapeutic dosage of gentamicin on renal function in white white rats (Rattus norvegicus). The subjects of this experiment were 24 healthy white rats, age 3-5 months and weigh 110-120 grams, which were organized into three different groups based on the dosage of gentamicin injected: control group, the treatment group 1 was given gentamicin at a dose of 4 mg / kg / day and 2 treatment groups were administreted by gentamicin 8 mg / kg / day in 7 days. The data found in this study were analyzed by Kruskal Wallis statistical test. This study showed that there was a significant effect of therapeutic dosage of gentamicin on renal function in white rats as shown by the p-value = 0.000 (<0.05). The average value of renal necrosis is highest in the treatment group 2 that is equal to 11.951% and the lowest renal necrosis in the control group that is equal to 0.581%.